PENANGANAN STRESS DENGAN METODE DZIKIR LISAN DI PONDOK PESANTREN TETIRAH DZIKIR BERBAH SLEMAN - Najuba Zain; Irena Wahyu Damayanti; Nikmatul Choyroh Pamungkas; Nadia Saphira (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2018)
Today's mental health issues draw great attention from the public, especially observers of health policy. Where today, mental disability is a problem that is the responsibility of all of us. Islam is a religion that gives peace to every human being through dzikir which is spoken orally, performed with the ear and cool in the heart while according to psychology it is called healing word. This study aims to determine the effect of the method of oral dhikr in dealing with mental disability problems associated with stress disorder, using field research research methods or field research with a type of qualitative research. Data collection carried out in this study through literature books, interviews and direct observation. The method of oral dhikr is applied to improve mental health carried out after prayer with dzikir together with caregivers. The results showed that the process of oral dhikr therapy in Pondok Tetirah Dzikir was quite effective in reducing and curing patients suffering from stress disorder.